Clinical performance indicators for monitoring the management of cutaneous melanoma: a population-based perspective. Issue 5 (19th July 2022) - Buja, Alessandra; Rugge, Massimo; De Luca, Giuseppe; Zorzi, Manuel; Cozzolino, Claudia; Vecchiato, Antonella; Del Fiore, Paolo; Tropea, Saveria; Bortolami, Alberto; Benini, Patrizia; Rossi, Carlo Riccardo; Mocellin, Simone
Abstract : The prognosis of cutaneous malignant melanoma (CMM) is based on disease progression. The highly heterogeneous clinical-pathological characteristics of CMM necessitate standardized diagnostic and therapeutic interventions tailored to cancer's stage. This study utilizes clinical performance indicators to assess the quality of CMM care in Veneto (Northeast Italy). This population-based study focuses on all incidences of CMMs registered by the Veneto Cancer Registry in 2015 (1279 patients) and 2017 (1368 patients). An interdisciplinary panel of experts formulated a set of quality-monitoring indicators for diagnostic, therapeutic, and end-of-life clinical interventions for CMM. The quality of clinical care for patients was assessed by comparing the reference thresholds established by experts to the actual values obtained in clinical practice. The prevalence of stage I-CMM decreased significantly from 2015 to 2017 (from 71.8 to 62.4%; P < 0.001), and almost all the pathology reports mentioned the number of nodes dissected during a lymphadenectomy. More than 90% of advanced CMMs were promptly tested for molecular BRAF status, but the proportion of patients given targeted therapies fell short of the desired threshold (61.1%). The proportion of stage I–IIA CMM patients who inappropriately underwent computerized tomography/MRI/PET dropped from 17.4 to 3.3% ( P < 0.001). Less than 2% of patients received medical or surgical anticancer therapies in the month preceding their death. In the investigated regional context, CMM care exhibited both strengths and weaknesses. The evaluated clinical indicators shed essential insight on the clinical procedures requiring corrective action. It is crucial to monitor clinical care indicators to improve care for cancer patients and promote the sustainability of the healthcare system.